P07 Improving patient care in psoriatic arthritis through quality improvement and audit against the National Institute for Health and Care Excellence NG65 guidelines. (20th April 2020) - Papadopoulos, Elena J; Chan, Antoni; Rigler, Kathryn; Kachwaha, Avaish; Gunn, Jessica; Zabbey, Nneoma; Walsh, Emma
Abstract: Background: NICE guidelines (NG65) for diagnosis and management of spondyloarthritis (SpA) in over 16s provide evidence-based recommendations for provision of care and services for patients, with an aim to improving quality of care. There often appears to be misdiagnosis/under diagnosis of psoriatic arthritis (PsA), as well as unmet needs of achieving treatment to target and low disease activity. Our objective was to audit our PsA service against the guidelines to benchmark current service provision compared to the National recommendations, highlighting potential key areas to improve quality of SpA and PsA patient care and enable service development including our new electronic patient pathway. Methods: The NICE baseline assessment tool was used to audit 100 patients diagnosed with PsA, attending the outpatient rheumatology clinic between 2017-2019. The mean age was 54, with a 3:2 female to male ratio. 30% of patients included were on a biologic disease modifying anti-rheumatic drug (bDMARD). Data was collected from clinic letters/medical/physiotherapy records. Data was collated to identify areas of compliance of our service against the guidelines, with the key outcomes scrutinised being assessment and diagnosis, imaging, information and support, pharmacological management and long-term condition management. Results: 78% of patients with PsA had documentation of meeting the CASPAR or peripheral ASAS Criteria. 83% of patients who had symptomatic hands/feet obtained X-rays, and 82% had imaging of other peripheral or axial sites. 58% of patients with PsA had documented evidence of having received information on PsA. Out of 100% of patients that were started on a conventional synthetic DMARD (csDMARD), 83% that were on monotherapy were escalated to either an additional csDMARD or a bDMARD. Largely by month 3 the csDMARD was switched or the patient started combination therapy, in comparison to those that started a bDMARD which occurred largely around month 6. 100% of patients had access to flare management advice and flare clinic, but only 30% had documented discussions about cardiovascular (CV) and skin cancer risks on anti-TNF therapy. Subsequent action plans for service improvement included: a best practice pathway developed on the electronic patient records (EPR), including the CASPAR and ASAS criteria, the Group for Research and Assessment of Psoriasis (GRAPPA) 6 domains of PsA, CV and skin cancer risk. All patients are seen in the Nurse/therapist led education sessions for information on the disease. Conclusion: Performing an audit of patients against the NG65 guidelines ensured that we were using real-world data to benchmark our service, enabling robust action plans to be developed to address low compliance areas. Consequently, the audit allowed us to justify changing and developing the service for improved patient care. Disclosures: E.J. Papadopoulos: Other; Paid work with Novartis Pharmaceuticals. A. Chan: Member of speakers' bureau; Novartis, Celgene, Janssen, Sanofi. Other; Advisory Board for: Novartis, Celgene, Lilly. K. Rigler: Other; aid work for Novartis Pharmaceuticals. A. Kachwaha: None. J. Gunn: None. N. Zabbey: None. E. Walsh: None.